2011
DOI: 10.1107/s160053681102602x
|View full text |Cite
|
Sign up to set email alerts
|

Di-μ-acetato-bis(dimethylformamide)pentakis(μ-N,2-dioxidobenzene-1-carboximidato)tetrakis(1-ethylimidazole)pentamanganese(III)manganese(II)–diethyl ether–dimethylforamide–methanol–water (1/1/1/1/0.12)

Abstract: Key indicators: single-crystal X-ray study; T = 100 K; mean (C-C) = 0.007 Å; disorder in solvent or counterion; R factor = 0.059; wR factor = 0.148; data-toparameter ratio = 16.4.The title compound [Mn 6 (C 7 ExperimentalCrystal data

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…For related manganese and vanadium metallacrown structures, see: Lah & Pecoraro (1989) and , respectively. For related Mn(II)[15-MC Mn(III)N(shi) -5)] structures and synthetic procedures, see: Kessissoglou et al (1994), Dendrinou-Samara et al (2001, 2002, 2005; Emerich et al (2010); Tigyer et al (2011Tigyer et al ( , 2012. For an explanation on how to calculate the s/h ratio, see: Stiefel & Brown (1972).…”
Section: Related Literaturementioning
confidence: 99%
“…For related manganese and vanadium metallacrown structures, see: Lah & Pecoraro (1989) and , respectively. For related Mn(II)[15-MC Mn(III)N(shi) -5)] structures and synthetic procedures, see: Kessissoglou et al (1994), Dendrinou-Samara et al (2001, 2002, 2005; Emerich et al (2010); Tigyer et al (2011Tigyer et al ( , 2012. For an explanation on how to calculate the s/h ratio, see: Stiefel & Brown (1972).…”
Section: Related Literaturementioning
confidence: 99%
“…For a general review of metallacrowns, see: Mezei et al (2007). For related Mn(II)[15-MC Mn(III)N(shi) -5)] structures and related synthetic procedures, see: Kessissoglou et al (1994); Dendrinou-Samara et al (2001, 2002, 2005; Emerich et al (2010); Tigyer et al (2011). For an explanation on how to calculate , see: Addison et al (1984).…”
Section: Related Literaturementioning
confidence: 99%
“…The family of manganese-based 15-MC-5 complexes, which consists of a 15 membered ring with a -[Mn(III)-N-O] 5 -repeat unit and a central Mn(II) ion, have shown better antibacterial activity than simple manganese-herbicide complexes (Dendrinou-Samara et al, 2002, 2005). The first few Mn-based 15-MC-5 complexes were made with pyridine molecules bound to the structure (Kessissoglou et al, 1994;Dendrinou-Samara et al, 2001, 2002, 2005; however, it has recently been shown that imidazole can also be used to produce a Mn-based 15-MC-5 complex (Emerich et al, 2010;Tigyer et al 2011).…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations